Assessment of Information Literacy and Computer Literacy among Post Graduate Students: a Case Study of Kuvempu University Library Users - Ramakrishnegowda, K. C.; Walmiki, R. H. (Journal of Information and Knowledge, 2014)
A study was conducted in Kuvempu University to know the entry-level computer literacy and information literacy of the post-graduate students. Questionnaire was used as a data collection tool. The study found that the majority of the respondents lack awareness regarding directories, encyclopedias, subject journals, yearbooks, etc. As many as 66% of the students do not possess the ability to identify the key concepts in the given information environment. More than 44% of the respondents are not able to use the computers and many of them do not possess the knowledge of software, hardware, storage devices, etc. Nearly two-thirds of the total respondents are not able to use the Internet. The majority (75.03%) of the students opine that the computer literacy and information literacy programmes are “very important” for them. The authors suggest the University to take steps to impart computer literacy and information literacy programmes to the students studying in the Constituent Colleges for the bachelor’s degrees. And, such training should be continued at the post-graduate level also to attain the advanced level skills and expertise. Stresses the role of Librarians working in Colleges and Universities to impart such education to students.